A comparative study of thrombolysis in cases of prosthetic mitral valve replacement dysfunction between intravenous alteplase and intravenous urokinase - Maulik Sharma; Shefali Goyal; Rajkumar Yadav (Heart India)
Background: Comparison between intravenous thrombolysis with alteplase and urokinase in cases of mitral valve replacement prosthesis dysfunction due to thrombus formation over the prosthetic valve. Materials and Methods: Three hundred patients of mitral valve replacement prosthesis dysfunction for thrombolysis of thrombus formation over the prosthetic valve were taken up for study at our hospital from September 2022 to May 2024, which were randomly allocated to two groups – intravenous alteplase treatment group (Group 1, n = 150) and intravenous urokinase treatment group (Group 2, n = 150). The parameters which were included in the study were mean gradient across the valve, efficiency of thrombolysis, side effects, and long-term effects of treatment of the patients in these groups. A statistical study was undertaken. Results: There was no significant difference in pre- and posttreatment in both the groups (P = 0.125 and P = 0.230); the total effective rates of the groups were 98% (147/50), 95% (142.5/100), the differences of which were not significant in statistics (P = 0.75 > 0.05). The adverse reaction rates of the groups for Group A was 7.5% (11.25/150) for Group B 10% (15/150) and there were no significant differences (P = 0.256 > 0.05); No change as it is data that we got in our study; the differences of flow across the valve, good prognosis rates, and mortality rates among the groups had no statistical significance (P = 0.421, 0.467, and 0.362 >0.05). The duration of mitral valve replacement for every patient is different and does not follow a particular timeline. The mean gradient range across the prosthetic valve has no relation with thrombolysis of the prosthetic valve. Conclusions: The use of alteplase and urokinase intravenously for thrombolysis in cases of post-MVR valve dysfunction has equivalent therapeutic effects.